2017
DOI: 10.1038/onc.2017.44
|View full text |Cite
|
Sign up to set email alerts
|

The histone demethylase KDM3A, and its downstream target MCAM, promote Ewing Sarcoma cell migration and metastasis

Abstract: Ewing Sarcoma is the second most common solid pediatric malignant neoplasm of bone and soft tissue. Driven by EWS/Ets, or rarely variant, oncogenic fusions, Ewing Sarcoma is a biologically and clinically aggressive disease with a high propensity for metastasis. However, the mechanisms underpinning Ewing Sarcoma metastasis are currently not well understood. In the present study, we identify and characterize a novel metastasis-promotional pathway in Ewing Sarcoma, involving the histone demethylase KDM3A, previou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
75
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(83 citation statements)
references
References 91 publications
8
75
0
Order By: Relevance
“…However, the opposite was true in KDM3A‐knockout rats. We and others have found that ETS‐1 is a downstream target of KDM3A, and our latest experiment verified that KDM3A could directly bind to the promoter of ETS‐1 and control H3K9 methylation in myocardial ischaemia‐reperfusion injury. KDM3A overexpression displayed higher ETS‐1 transcriptional activity concomitant with reduced inflammation, ROS and apoptosis.…”
Section: Discussionsupporting
confidence: 67%
“…However, the opposite was true in KDM3A‐knockout rats. We and others have found that ETS‐1 is a downstream target of KDM3A, and our latest experiment verified that KDM3A could directly bind to the promoter of ETS‐1 and control H3K9 methylation in myocardial ischaemia‐reperfusion injury. KDM3A overexpression displayed higher ETS‐1 transcriptional activity concomitant with reduced inflammation, ROS and apoptosis.…”
Section: Discussionsupporting
confidence: 67%
“…Having a longer DNA containing sequences for tissue-specific expression of the gene is essential for further understanding the roles of other regulators [17]. In line with this hypothesis, recently, the Ets sequence in the 10 kilo-bp upstream region has been shown to regulate the expression of huMET-CAM/MUC18 gene [95]. We have also engaged in this task by screening in a phage library containing the human genomic sequences and obtained several phage clones which contain at least 4 kilo-bp of in the upstream region of the promoter region of the gene for future studies [96].…”
Section: Transcriptional Regulationmentioning
confidence: 99%
“…Recently, a number of studies have implicated KDM3A (JMJD1A/JHDM2A), a member of the KDM3 subfamily with specificity for removal of mono and di-methyl marks from H3K9, in tumor/metastasis promotion, chemoresistance and other phenotypes, in cancers of epithelial origin (including the common cancers of breast 4 , prostate 5 and colon 6 ), liver 7 , and the hematopoietic system 8 . Additionally, recent studies have implicated KDM3A in solid malignancies of childhood, including the metastasis of neuroblastoma 9 , a malignant pediatric tumor of peripheral nervous system origin, and both tumorigenesis and metastasis of Ewing Sarcoma 10, 11 , a pediatric sarcoma of bone and soft tissue.…”
Section: Epigenetic Mechanisms In Cancer and Kdm3amentioning
confidence: 99%
“…The biology of Ewing Sarcoma metastasis is incompletely understood and, surprisingly, recent studies indicate that the driver oncofusion, EWS/Fli1, attenuates rather than augments metastatic properties of the cancer 12, 13 . The biology of KDM3A is very interesting in this context, in that it positively regulates many pro-metastatic genes repressed by EWS/Fli1 11 . As a promoter of tumorigenesis and metastasis, KDM3A is a therapeutic target of interest in Ewing Sarcoma.…”
Section: Expert Opinionmentioning
confidence: 99%
See 1 more Smart Citation